2004
DOI: 10.1029/2004gl019412
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime removal of NOx in the summer marine boundary layer

Abstract: [1] The nitrate radical, NO 3 , and dinitrogen pentoxide, N 2 O 5 , are two important components of nitrogen oxides that occur predominantly at night in the lower troposphere. Because a large fraction of NO 2 reacts to form NO 3 and N 2 O 5 during the course of a night, their fate is an important determining factor to the overall fate of NO x (=NO and NO 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
147
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(162 citation statements)
references
References 22 publications
15
147
0
Order By: Relevance
“…In addition; nighttime secondary NO 3 − formation involves the hydrolysis of dinitrogen-pentaoxide (N 2 O 5 ) through the heterogeneous reaction on aerosol surfaces and higher relative humidity enhances the heterogeneous hydrolysis of N 2 O 5 (Ravishankara et al, 1997;Jacob, 2000;Pathak et al, 2009). Brown et al (2004) have suggested that the conversion efficiency of NO x to HNO 3 during nighttime can be equivalent to the daytime photochemical conversion. Moreover, Vrekoussis et al (2006) have found that ~55-65% of the total production of nighttime HNO 3 and NO 3 − were through the heterogeneous reactions of NO 3 radical in an anthropogenically-influenced eastern Mediterranean marine boundary layer.…”
Section: Sulphur and Nitrogen Oxidation Ratios (Sor And Nor)mentioning
confidence: 99%
“…In addition; nighttime secondary NO 3 − formation involves the hydrolysis of dinitrogen-pentaoxide (N 2 O 5 ) through the heterogeneous reaction on aerosol surfaces and higher relative humidity enhances the heterogeneous hydrolysis of N 2 O 5 (Ravishankara et al, 1997;Jacob, 2000;Pathak et al, 2009). Brown et al (2004) have suggested that the conversion efficiency of NO x to HNO 3 during nighttime can be equivalent to the daytime photochemical conversion. Moreover, Vrekoussis et al (2006) have found that ~55-65% of the total production of nighttime HNO 3 and NO 3 − were through the heterogeneous reactions of NO 3 radical in an anthropogenically-influenced eastern Mediterranean marine boundary layer.…”
Section: Sulphur and Nitrogen Oxidation Ratios (Sor And Nor)mentioning
confidence: 99%
“…Measurements of NO 3 have been overestimated by model calculations in several studies (Mihelcic et al, 1993;Sommariva et al, , 2007, with those of nighttime OH and HO 2 radicals typically underestimated, indicating poor understanding of nighttime tropospheric oxidation processes (Kanaya et al, 1999(Kanaya et al, , 2002(Kanaya et al, , 2007aEmmerson and Carslaw, 2009;Geyer et al, 2003;Faloona et al, 2001;Martinez et al, 2003;Ren et al, 2006). While a number of nighttime studies at ground level close to local sources of NO have observed a limited role of NO 3 in nighttime radical production owing to surface losses of NO 3 and the rapid reaction between NO 3 and NO (Salisbury et al, 2001;Fleming et al, 2006;Sommariva et al, 2007;Kanaya et al, 1999Kanaya et al, , 2002Kanaya et al, , 2007aEmmerson and Carslaw, 2009;Faloona et al, 2001;Martinez et al, 2003;Ren et al, 2003Ren et al, , 2005Ren et al, , 2006Volkamer et al, 2010), several studies of NO 3 and N 2 O 5 above ground level and in more remote regions have indicated a more significant role for NO 3 in nighttime radical production and tropospheric oxidation (Platt et al, 1980;Povey et al, 1998;South et al, 1998;Aliwell et al, 1998;Allan et al, 2002;Stutz et al, 2004;Brown et al, 2003Brown et al, , 2004Brown et al, , 2006Brown et al, , 2007Brown et al, , 2009...…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of NO 3 and N 2 O 5 were made downwind of New York City during the New England Air Quality Study (NEAQS) by cavity ringdown spectroscopy (CRDS) onboard the National Oceanic and Atmospheric Administration (NOAA) research vessel (R/V) Ronald H. Brown in summers 2002 Brown et al, 2004;Aldener et al, 2006) and 2004 . While measurements of nighttime composition in New York City led to the conclusion that O 3 -initiated oxidation processes were dominant at night (Ren et al, 2003(Ren et al, , 2006, those made during NEAQS indicated little influence of O 3 -initiated VOC oxidation at night, with oxidation of biogenic VOCs dominated by NO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of NO x varies from > 100 ppb (parts per billion) next to roads (Carslaw, 2005;Pandey et al, 2008) to low ppt (parts per trillion) in the remote atmosphere . Direct transport of NO x from polluted to remote regions is not efficient, because NO x is removed from the atmosphere on a timescale of around a day by the reaction of NO 2 with OH and the hydrolysis of N 2 O 5 on aerosol surfaces (Brown et al, 2004;Dentener and Crutzen, 1993;Riemer et al, 2003). Instead, reservoir species such as peroxyacetyl nitrate are made in polluted regions (where concentrations in both NO x and peroxyacetyl precursors such as acetaldehyde are elevated) and are subsequently transported to remote regions, where they thermally break down to release NO x (Fischer et al, 2014;Moxim et al, 1996;Roberts et al, 2007).…”
Section: Introductionmentioning
confidence: 99%